Preoperative easily misdiagnosed pure spinal epidural cavernous hemangioma: clinical-radiologic-pathologic correlations - Li, Jingwen; Guo, Zhongyin; Liu, Yang; Xu, Mengqi; Wang, Peng; Chen, Feng; Zeng, Yuecheng; Peng, Peng (Frontiers in Neurology, 2025)
ObjectivePure spinal epidural cavernous hemangiomas (PSECHs) are exceedingly rare vascular anomalies, often underreported and prone to misdiagnosis. This study aims to synthesize existing literature alongside seven cases from our institution to elucidate the clinical, imaging, and pathological characteristics of PSECHs for improving the clinical diagnosis and treatment of this disease.MethodsThe clinical data of published literature and seven patients diagnosed with PSECHs admitted to the Department of Neurosurgery of Xiangyang Central Hospital from January 2013 to November 2022 were retrospectively analyzed for pre- and post-operative imaging findings, clinical manifestations, treatment history, pathologic characteristics, and treatment effects.ResultsApproximately a hundred cases of PSECHs had been documented in the literature, with a clinical misdiagnosis rate reaching 91.3%. Among the seven patients studied, five were female, with a mean age of 49.4 years. In five cases, the lesions were located in the thoracic vertebral segment, while the cervical and lumbar vertebral segments each accounted for one case. One patient presented exclusively with radicular symptoms, four exhibited solely spinal cord symptoms, and two experienced both spinal cord and radicular symptoms. Two cases were initially misdiagnosed as meningiomas prior to surgery (2/7, 28.6%), with one case not accurately identified during the operation, leading to an erroneous aspiration as surgical blood seepage. Alongside the preoperative diagnosis of vascular lesion in case 7, we experienced a 42.9% (3/7, 42.9%) rate of preoperative misdiagnosis. Six lesions (6/7, 85.7%) demonstrated isointensity on T1-weighted images and hyperintensity on T2-weighted images, with all lesions exhibiting homogeneously strong enhancement. The “double tail” sign and fusiform shape in the sagittal view were observed in six lesions. Complete resection was achieved in all patients, resulting in excellent clinical outcomes. No symptoms or lesions recurred during the follow-up period.ConclusionPSECHs are rare vascular malformations and easily misdiagnosed preoperatively. Accurate identification of the imaging characteristics of PSECHs is crucial for their diagnosis and subsequent management. Surgical total excision remains an effective treatment modality, and early intervention is recommended to prevent acute hemorrhagic events, which could adversely impact patient outcomes.